Glomerular Exostosin as a Subtype and Activity Marker of Class 5 Lupus Nephritis. Issue 7 (July 2022) - Wang, Chengyu; Liu, Yang; Zhang, Mingchao; Yang, Fan; Xu, Feng; Shi, Shaolin; Zeng, Caihong; Chen, Xin; Miao, Yiqi; Liu, Zhengzhao; Hu, Weixin
Visual Abstract: Abstract : Background and objectives: There have been only several studies on the correlation between glomerular exostosin expression and membranous lupus nephritis. In this study, we validate the previous findings in Chinese patients with class 5 lupus nephritis. Design, setting, participants, & measure: One hundred sixty-five patients with class 5 lupus nephritis and varying numbers of control patients were included. Exostosin1/exostosin2 staining was performed by immunohistochemistry, and the staining intensity was quantified using an imaging analysis system. Between-group comparisons were tested for statistical significance using the Pearson chi-squared test, the Fisher exact test, the unpaired t test, the Mann–Whitney U test, or one-way ANOVA. Results: In total, 46% of patients with class 5 lupus nephritis, 9% of patients with class 5 + 3/4 lupus nephritis, and none of the other classes of lupus nephritis were exostosin positive. Only three patients were exostosin positive among the 61 patients with other secondary membranous nephropathy. The exostosin-positive rate in nephrotic patients was significantly higher than that in patients without nephrotic syndrome ( P <0.001), and the exostosin staining intensities of the patients with exostosin-positive class 5 were positively correlated with proteinuria ( r =0.53; P <0.001). Compared with the patients with exostosin-negative cases, the patients with exostosin-positive cases had higher proteinuria levels (3.9 [interquartile range, 2.0–6.3] g/d versus 2.3 [interquartile range, 1.0–3.6] g/d; P <0.001); lower scores of activity index (1 [interquartile range, 1–2] versus 2 [interquartile range, 1–3]; P =0.001), chronicity index (1 [interquartile range, 0–2] versus 2 [interquartile range, 1–2]; P =0.02), and tubular atrophy score (0 [interquartile range, 0–1] versus 1 [interquartile range, 0–1]; P =0.008); a higher proportion of extensive subepithelial deposition (62% versus 27%; P <0.001); a similar treatment response; and comparable time to kidney end point. Among the 47 patients with class 5 who underwent repeat biopsy, 97% of those with exostosin-negative cases remained negative, whereas 44% of those with exostosin-positive cases were still positive. The rate of histologic transition in the patients with exostosin-negative class 5 was significantly higher than that in the patients with exostosin-positive class 5 (59% versus 22%; P =0.03). Conclusions: Exostosin positivity occurred frequently in patients with class 5 lupus nephritis, and patients with exostosin-positive cases had more severe proteinuria and a lower rate of histologic transition than the exostosin-negative patients.